Perbandingan Hasil Tangkapan Cumi Alat Tangkap Lambayang Yang Menggunakan Lampu Suntik dan Umpan Buatan di Kelurahan Tanjung Kramat Kota Gorontalo - Ahili, Fingki; Baruadi, Alfi Sahri Remi; Salam, Aziz (Riviera Publishing, 2025)
This study aims to compare the effectiveness of lambayang fishing gear using two different methods: the use of injectable lights and artificial bait in squid fishing activities in the waters of Tanjung Kramat Village, Gorontalo City. Data was collected during 20 fishing trips by 20 fishermen. The results showed that the use of injectable lights resulted in much higher catches, namely 90.68% of the total squid catch (4,865 heads), compared to 9.32% (500 heads) using artificial bait. These findings suggest that the injectable lamp is more effective due to the squid's phototaic response to light. Although artificial feeds can still be an alternative, their effectiveness is limited to certain environmental conditions. This research emphasizes the importance of fishing gear selection to improve catch efficiency and encourage sustainable fishing practices.